Development of Highly Efficient Energy Harvester Based on Magnetic Field Emanating From a Household Power Line and Its Autonomous Interface Electronics - Jung, Seyoon; Kim, Sihyeok; Cho, Wonjun; Lee, Keekeun (IEEE Sensors Journal, 2023)
A magnetic energy harvester and its interface electronics are developed to operate a surface acoustic wave (SAW) oscillator sensor that requires at least 5-6 V dc (50-100 mW) to drive and transmit the measured sensor signals to the reader system wirelessly via antennas. The developed energy harvester system comprises a magnetic energy harvester with a coil wound around a magnetic core, an energy storage interface, and a power management interface. From a 220-V, 3-A household ac power line, a 12-V dc is harvested in the storage capacitor via a 5-min energy scavenging process to activate the SAW oscillator sensor. After 2 min of operation using the sensor system, the power management interface is completely shut down to recharge the storage capacitor and then restarted after sufficient charges are accumulated in the storage capacitor to reoperate the SAW oscillator sensor. This autonomous sequence is continuously repeated. The entire interface electronics is developed on a single printed circuit board (PCB) to reduce the energy loss by the board and to facilitate installation in the desired applications. A simulation is performed in COMSOL to determine the optimal energy harvester parameters and to predict the magnetic flux density that forms the induced current around the ferrite magnetic core based on the magnetic core shape. Experimental results show that the developed energy harvester system can harvest sufficient energy from the household power line in a short period to operate the complex RF SAW sensor and the sensor interface electronics. Furthermore, it can be used to operate the SAW oscillator sensor for the time required to obtain valid information to be transmitted wirelessly to the reader system.
Keywords: Autonomous interface electronic; Energy Harvester; Full-wave rectifiers; Household power line; Interface electronics; Magnetic field energy; Magnetic field energy harvester; Power lines; Power-on resets; Sensor systems; Surface acoustic wave oscillator sensor; Surface acoustic wave oscillators; Surface acoustic waves; Wireless transmissions; Autonomous interface electronics; full-wave rectifier; household power line; magnetic field energy harvester; power-on reset; surface acoustic wave (SAW) oscillator sensor; wireless transmission